Icon, Brand, Myth: The Calgary Stampede - Max Foran (The West Unbound:Social and Cultural Studies, 2008)
An investigation of the meanings and iconography of the Stampede: an invented tradition that takes over the city of Calgary for 10 days every July. Since 1923, archetypal "Cowboys and Indians" are seen again at the chuckwagon races, on the midway, and throughout Calgary. Each essay in this collection examines a facet of the experience-from the images on advertising posters to the ritual of the annual parade. This study of the Calgary Stampede as a social phenomenon reveals the history and sociology of the city of Calgary and the social construc-tion of identity for western Canada as a whole.